Enhanced adhesion of elastic materials to small-scale wrinkles - Davis, Chelsea S (Langmuir : the ACS journal of surfaces and colloids, 2012)
The adhesive properties of a material can be greatly affected simply by wrinkling its surface. We show the importance of selecting the wrinkle feature sizes (amplitude, b; and wavelength, λ) that complement the material-defined length scale related to the adhesion energy and modulus. A rigid circular cylindrical punch patterned with aligned wrinkles ranging in amplitude from 0.5 to 5.0 μm with a fixed aspect ratio of 0.1 is used to characterize the adhesion of elastic films of smooth poly(dimethyl siloxane) (PDMS). The cross-linker concentration used to form the PDMS layers is varied to determine the impact of material properties on wrinkled surface adhesion. The elastic films have an average thickness of 240 μm and the average probe radius is 1 mm, leading to a confined contact scenario. The separation stress and work of debonding are presented for each cross-linker concentration with testing rates ranging over 3 orders of magnitude. For stiffer films (10 wt % cross-linker, E' ≈ 3.00 MPa), small wrinkles (b ≈ 0.5 μm) increase the separation stress by nearly 200% relative to a smooth interface whereas large wrinkles (b ≈ 5.0 μm) are shown to reduce adhesion significantly. A substantial increase in the debonding energy is also observed for these small-amplitude wrinkles contacting stiff materials. No discernible impact of wrinkled surface topography on the adhesion of softer (2 and 4 wt % cross-linker, 0.05 MPa < E' < 0.30 MPa) films is measured